1975
DOI: 10.1111/j.1365-2141.1975.tb00529.x
|View full text |Cite
|
Sign up to set email alerts
|

The Procoagulant Factor of Leukaemic Promyelocytes: Demonstration of Immunologic Cross Reactivity with Human Brain Tissue Factor

Abstract: A procoagulant activity was found in the immature cells from patients with acute promyelocytic leukaemia. It was demonstrated that this activity was related to tissue factor. The protein component of tissue factor from brain extract was purified by Nemerson's technique and injected into rabbits to obtain anti-TF antibodies. Similar antibodies were produced against the promyelocyte extract. The anti-brain tissue factor antibodies neutralized the tissue factor activity of promyelocyte extract, and antibodies aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

1977
1977
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…One of the mRNAs (corresponding to cDNA clone 482 [14]) appeared within 20 min after exposure of the cells to PDGF or FGF, reached a maximal level by 2 h, and rapidly declined thereafter ( (14), and the levels of three immediate-early RNAs were determined at the indicated times thereafter by slot blot hybridization to [32P]cDNA probes. In the FGF experiments, 6 ,ug of total cellular RNA was used, and in the PDGF experiments, 2 ,ug was used. (B) Nuclear run-on transcription of nuclei isolated from quiescent cells or after quiescent cells were exposed to 50 ng of PDGF per ml for 10 or 30 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the mRNAs (corresponding to cDNA clone 482 [14]) appeared within 20 min after exposure of the cells to PDGF or FGF, reached a maximal level by 2 h, and rapidly declined thereafter ( (14), and the levels of three immediate-early RNAs were determined at the indicated times thereafter by slot blot hybridization to [32P]cDNA probes. In the FGF experiments, 6 ,ug of total cellular RNA was used, and in the PDGF experiments, 2 ,ug was used. (B) Nuclear run-on transcription of nuclei isolated from quiescent cells or after quiescent cells were exposed to 50 ng of PDGF per ml for 10 or 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, a variety of cell ligands stimulate hTF production by human endothelial cells or monocytes (16,18,20,22). Although the cellular TF response to these various ligands may be related to the role of TF in blood clotting, it is possible that TF (or its free extracellular domain) has other functions, including a role in normal cell proliferation and neoplasia (6). For example, since hTF binds factor VII to form a proteolytically active complex that cleaves factor IX and factor X (21), TF may activate other proteases that affect cell-cell or cell-matrix interactions related to cell movement and/or growth.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue factor is a potent procoagulant which may be important in the pathogenesis of intra-and extravascular coagulation in a variety of disorders (14)(15)(16)(17)(18)(19)(20)(21)(22)46). Recent evidence has suggested that tissue factor is present in cell membranes in an inactive form which is "activated" by an unknown mechanism as a result of the interaction of the cell with various agents (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…Unperturbed cells manifest little, if any, tissue factor activity, and "activation" by endotoxin, antigens, mitogens, or enzymes is required for expression of latent coagulant activity (3,6). A central role has been suggested for white cell tissue factor in the initiation of intravascular coagulation secondary to progranulocytic leukemia (14)(15)(16) and Gram-negative sepsis (17)(18)(19)(20). Recent evidence has also suggested that tissue factor activity generated by immunocompetent cells may play a role in the deposition of fibrin seen in association with delayed hypersensitivity reactions (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Acute leukemia is the most representative malignancy in which DIC readily occurs (3). In acute leukemia, the trigger of DIC has been identified as a procoagulant activity known as tissue factor (TF), which is present in leukemic cells (4)(5)(6)(7). TF activity can be measured in virtually all leukemia patients by a simple clotting assay using bone marrow cells (2,8).…”
Section: Introductionmentioning
confidence: 99%